2015
DOI: 10.3109/14767058.2015.1052398
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal HLA-G 14 bp gene polymorphism in pregnancy-induced hypertension, preeclampsia, intrauterine growth restricted and normal pregnancies

Abstract: With this study we filled several gaps occurring in previous studies: we analyzed a very well-defined population of PE, PIH and IUGR pregnancies, considering both fetal and maternal HLA-G 14 bp polymorphism, individually and jointly. Our findings showed that fetal and maternal HLA-G 14 bp genotypes are not associated with increased risk for the development of obstetrical complications, suggesting that this polymorphism has no immuno-modulatory role in the development of PE, PIH or IUGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
11
2
1
Order By: Relevance
“…Many studies have shown that the HLA-G level was associated with complications of pregnancy like recurrent miscarriages and preeclampsia (14,15,29,35,36,37). Our results did not reveal any association between the HLA-G 14 bp polymorphism and the 1597∆C polymorphism tagging the HLA-G*01:05N null allele and the risk of pre-eclampsia in Slovak women.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Many studies have shown that the HLA-G level was associated with complications of pregnancy like recurrent miscarriages and preeclampsia (14,15,29,35,36,37). Our results did not reveal any association between the HLA-G 14 bp polymorphism and the 1597∆C polymorphism tagging the HLA-G*01:05N null allele and the risk of pre-eclampsia in Slovak women.…”
Section: Discussioncontrasting
confidence: 83%
“…The 14 bp insertion polymorphism has been associated with lower levels of soluble HLA-G suggesting its role in PE development (13,27). We did not fi nd any statistically signifi cant differences in HLA-G 14 bp ins/del allele and genotype distribution between women with PE and controls as given by others (19,20,28,29). The newest meta-analysis of several smaller studies also revealed no associations between the HLA-G 14 bp ins/del genotype and development of PE (30).…”
Section: Discussioncontrasting
confidence: 42%
“…However, we did not find any associations (Tables S1-S3). While the HLA-G 14-bp ins/del polymorphism is related to HLA-G expression in in vitro studies, several other polymorphisms may influence the expression levels in vivo (57)(58)(59). In fact, polymorphisms residing in the regulatory regions of the HLA-G gene, 5 ′ URR and 3 ′ UTR, have been shown to be in high linkage disequilibrium with the 14-bp ins/del polymorphism, and believed to affect the rate of transcription and mRNA stability conjointly (32,48).…”
Section: Discussionmentioning
confidence: 99%
“…The same genotype (14‐bp ins/ins) was more frequent in women with more than three recurrent spontaneous abortions compared to fertile controls . However, in several studies, no relationship of the 14‐bp ins/ins genotype was reported for pregnancy complications such as preeclampsia, restricted intrauterine growth, recurrent spontaneous abortion, and implantation failure …”
Section: Discussionmentioning
confidence: 97%